APPLICATIONS OF FOLKLORE ON CHILDREN WITH PRINT TECHNIQUES AS THE EDUCATION FACILITY PARENTS OF MILENNIAL GENERATION - Soelistyowati Soelistyowati (Proceeding of International Conference on Art, Language, and Culture, 2017)
Indonesia has various ethnic  rich in tradition, and rich in art. Every culture has its own folklore. In the era of rapidly growing digital information, children and parents are no longer familiar with folklore. This design was created to provide one solution to introduce Indonesian folklore to children and parents. Media delivery of folklore through children's clothing with print techniques. This design in addition to the aim of attracting children to know the folklore is also expected to be a means of education to parents of millennial generation. The results of this study are expected to be useful for the creative industries. The method used in qualitative description research.